Prognostic Impact of Genetic Polymorphism in Mineralocorticoid Receptor and Comorbidity With Hypertension in Androgen-Deprivation Therapy - Shiota, Masaki; Fujimoto, Naohiro; Imada, Kenjiro; Kashiwagi, Eiji; Takeuchi, Ario; Inokuchi, Junichi; Tatsugami, Katsunori; Kajioka, Shunichi; Uchiumi, Takeshi; Eto, Masatoshi (Frontiers in Oncology, 2018)
Mineralocorticoid receptor (MR) signaling which is closely associated with hypertension plays important roles in resistance to antiandrogen therapy in prostate cancer. However, its impact on the prognosis in androgen-deprivation therapy (ADT) has not been elucidated. Then, we investigated the impact of genetic variation in MR and comorbidity with hypertension on the prognosis in ADT. This study included 182 Japanese patients with prostate cancer treated with ADT, whose comorbidity status with hypertension were available. The associations of MR polymorphism (rs5522) and comorbidity with hypertension with clinicopathological parameters as well as progression-free survival and overall survival were examined. Clinicopathological characteristics were comparable between genetic variation in MR. However, homozygous variant in MR was associated with shorter time to castration resistance (P = 0.014) and any-cause death (P = 0.024). In patients’ background, presence of comorbidity with hypertension was showed the trend with lower PSA level at diagnosis and lower biopsy Gleason score, as well as significant association with less incidence of N1. Comorbidity with hypertension was associated with longer time to castration resistance (P = 0.043) and any-cause death (P = 0.046), which was diminished on multivariate analysis including age, PSA level at diagnosis, biopsy Gleason score, clinical stage, and the modality of hormonal therapy. Genetic variation in MR (rs5522) and comorbidity with hypertension were significantly and potentially associated with prognosis when treated with ADT, respectively. This suggests that the individual intensity of MR signaling may be associated with resistance to ADT and a promising biomarker in ADT.